All of work? All of life? Reconceptualising work‐life balance for the 21st century. (25th September 2018) - Kelliher, Clare; Richardson, Julia; Boiarintseva, Galina
Abstract: This paper argues that the study of work‐life balance to date has, in the main, adopted a restricted conception of both "work" and "life", which does not take account of recent developments in life worlds, working arrangements and employment relationships. "Life" has hitherto been viewed as largely comprising caring activities for dependent children, whereas "work" has been premised largely on a traditional model of work, characterised by full‐time, permanent employment with one employer and a conventional understanding of what work involves. This means that extant research and theory only provides a partial view of the work‐life needs and experiences of the workforce. In the paper, we propose extending conceptions of both work and life to incorporate different life worlds and social groups and different working arrangements and employment relationships.